(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study aimed to assess the effects of various soil types andorganic growing media on the growth of some tree seedlings. It wasconducted in the nursery of the Faculty of Forestry, University ofKhartoum, Shambat, during March-November 2006. Soil growing growthmedia consisted of sand, silt and clay, while the organic matter consistedof decomposed mango humus. Seeds of Tamarindus indica L., Albizialebbeck (L.) Benth. and Acacia senegal (L.) Wild. were directly sown inpolyethylene bags (10x20 cm). Seedlings shoot height, diameter, shootand root biomasses of all the species were positively significantly affectedby clay and silt media. Root growth was significantly greater in sand thanother media. Mango humus had negatively (P < 0.05) affected seedlings’growth of all the tested species. Nonetheless, seedlings’ survival rate wasfar better in the sand than in the other media. Silt and clay can be used assuitable growing media; pure sand may be used if production of seedlingswith well developed root system is envisaged. However, type and sourceof organic matter should be cautiously chosen before it can be confidentlyused as a suitable growing medium